2018
DOI: 10.1093/neuros/nyy316
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing Outcome Prediction Scores in Patients Undergoing Endovascular Thrombectomy for Large Vessel Occlusions Using Collateral Grade on Computed Tomography Angiography

Abstract: The addition of the collateral grade to outcome prediction scores resulted in better prediction of poor outcome after EVT for AIS compared to the prediction scores alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Our focus was routine stroke practice (139) and our comments on feasibility may not apply to specialist stroke centers. It takes time for scales to become established and our review did not include recently published scales, for example those designed to inform thrombectomy decisions (140). However, the literature describing these scales is increasing rapidly and soon there may be sufficient validation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus was routine stroke practice (139) and our comments on feasibility may not apply to specialist stroke centers. It takes time for scales to become established and our review did not include recently published scales, for example those designed to inform thrombectomy decisions (140). However, the literature describing these scales is increasing rapidly and soon there may be sufficient validation studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mean or median ages of the study participants ranged from 64.0 to 86.0 years, and the proportion of male participants ranged from 35.0 to 65.9%. Only one US study ( 24 ) specifically described the self-reported ethnicity of the patients (63.0–69.0% European ancestry); the other studies reported the place of patient recruitment [USA: 1 ( 32 ); Europe: 10 ( 22 , 23 , 26 29 , 31 , 33 35 ); Asia: 4 ( 25 , 30 , 36 , 37 )]. The training sample sizes ranged widely, from 109 to 1,401.…”
Section: Resultsmentioning
confidence: 99%
“…The training sample sizes ranged widely, from 109 to 1,401. Regarding the testing sample, two studies used hold-out test sets, respectively containing 208 patients ( 30 ) and 100 patients ( 35 ). The remaining studies performed cross-validation ( 23 26 , 28 , 29 , 31 34 , 36 , 37 ) or bootstrap approach ( 22 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…While missing statistical significance, there was an 18% difference in independent function for patients presenting initially to non-thrombectomy-capable centers for whom the ATA was visualized versus not visualized. Furthermore, it is possible that as with collateral grading, combining ATA visualization with outcome prediction scores will result in a better prediction of poor outcomes after transfer for EVT compared to the prediction scores alone [ 17 ].…”
Section: Discussionmentioning
confidence: 99%